Polymer Nanocomposite‐based Coatings for Corrosion Protection. Issue 23 (23rd October 2020) - Peng, Tingyu; Xiao, Ruihou; Rong, Zhenyang; Liu, Haibo; Hu, Qunyi; Wang, Shuhua; Li, Xu; Zhang, Jianming
Abstract: Corrosion of metals induces enormous loss of material performance and increase of cost, which has been a common and intractable issue that needs to be addressed urgently. Coating technology has been acknowledged to be the most economic and efficient approach to retard the metal corrosion. For several decades, polymers have been recognized as an effective anticorrosion coating material in both industries and scientific communities, as they demonstrate good barrier properties, ease of altering properties and massive production. Nanomaterials show distinctively different physical and chemical properties compared with their bulk counterparts, which have been considered as highly promising functional materials in various applications, impacting virtually all the fields of science and technologies. Recently, the introduction of nanomaterials with various properties into polymer matrix to form a polymer nanocomposite has been devoted to improve anticorrosive ability of polymer coatings. In this review article, we highlight the recent advances and synopsis of these high‐performance polymer nanocomposites as anticorrosive coating materials. We expect that this work could be helpful for the researchers who are interested in the development of functional nanomaterials and advanced corrosion protection technology. Abstract : The synthesis, properties, anticorrosion applications and corrosion protection mechanisms of polymer nanocomposite coatings based on various nanofillers have been summarized in this review. Furthermore, various rational processing strategies to promote a better polymer–particle interaction and technological advances are addressed.